Influence of oat extract on the eutrophicized waters of Lake Titicaca under controlled conditions in 2023 - Mamani Paricanaza, Peniel C. (2023)
This study addresses the problem of the release of contaminated wastewater in the interior bay of Lake Titicaca due to failures in the treatment plant. The main objective is to evaluate the influence of the application of oat extract (Avena sativa L.) on the eutrophication of lake waters under controlled conditions in 2023. A pure experimental design and a quantitative approach were used, including sample collection. and analysis of transparency, chlorophyll and total phosphorus. The application of oat extract is carried out under controlled conditions and is evaluated using the Trophic State Index. The results reveal specific characteristics of the extract, such as a humidity of 98.91%, 72 hours of exposure and a temperature of 11.2°C. In chemical terms, the pH is 7 and the concentration of phenolic compounds is 0.15 mg/l. However, the key results focus on its impact on eutrophication. Despite different doses, no significant decrease in eutrophication indicators, such as chlorophyll (a) and total phosphorus, is observed. This suggests that the doses of oat extract used might not be generating a significant effect in improving trophic status under the controlled conditions of the study.